Упростите выражение (18с^2 + 3с - 1)/ 1 - 6с - 6су + у И найдите его значение при с = -6; у = 5/12

Упростите выражение (18с^2 + 3с - 1)/ 1 - 6с - 6су + у И найдите его значение при с = -6; у = 5/12
Гость
Ответ(ы) на вопрос:
Гость
(18с^2 + 3с - 1)/(1 - 6с - 6су + у)= 18с^2 + 3с - 1= 18с*с + (6с - 3с)+ + 1 = 18с*с + 6с - 3с -1 = = 6с(3с + 1) - (3с + 1) = = (6с-1)(3с+1) 1 - 6с - 6су + у = (1+y) - 6с(1+y)== -(1+y)(6c-1) (6с-1)(3с+1)/-(1+y)(6c-1) = = (3с+1)/-(1+y) Найдите  его значение при с = -6; у = 5/12 (3с+1)/-(1+y) = [3*(-6) +1]/ -[ 1 + 5/12] = -17/-17/12 = 12
Не нашли ответ?
Ответить на вопрос
Похожие вопросы